2016
DOI: 10.1007/s11538-016-0220-y
|View full text |Cite
|
Sign up to set email alerts
|

Product-Form Stationary Distributions for Deficiency Zero Networks with Non-mass Action Kinetics

Abstract: In many applications, for example when computing statistics of fast subsystems in a multiscale setting, we wish to find the stationary distributions of systems of continuous-time Markov chains. Here we present a class of models that appears naturally in certain averaging approaches whose stationary distributions can be computed explicitly. In particular, we study continuous-time Markov chain models for biochemical interaction systems with non-mass action kinetics whose network satisfies a certain constraint. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
49
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(50 citation statements)
references
References 26 publications
1
49
0
Order By: Relevance
“…One of the most notable results in chemical reaction network theory is the deficiency zero theorem [2], which gives general conditions under which the reaction rate equations have a nontrivial stable equilibrium. More recently, this result has been extended to the chemical master equation, where it has been shown that, under the same conditions, the stochastic model has a product form stationary density [11,12]. The networks to which these theorems apply are known as complex balanced [13], and can be thought of as a generalization of the class of detailed balance networks.…”
Section: Introductionmentioning
confidence: 92%
“…One of the most notable results in chemical reaction network theory is the deficiency zero theorem [2], which gives general conditions under which the reaction rate equations have a nontrivial stable equilibrium. More recently, this result has been extended to the chemical master equation, where it has been shown that, under the same conditions, the stochastic model has a product form stationary density [11,12]. The networks to which these theorems apply are known as complex balanced [13], and can be thought of as a generalization of the class of detailed balance networks.…”
Section: Introductionmentioning
confidence: 92%
“…The underlying probability distributions are typically defined as solutions to a specific master equation (Paulsson, 2005;Veerman et al, 2018;Albert, 2019). Explicit solutions to the master equation, especially at steady state, can be found for models with few components Zhou and Liu, 2015) and/or with special structural properties (Kumar et al, 2015;Anderson and Cotter, 2016). Generally, however, explicit solutions are unavailable or intractable and one resorts to stochastic simulation or seeks a numerical solution to a finite truncation of the master equation (Munsky and Khammash, 2006;Borri et al, 2016;Gupta et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, exact characterisations of the copy-number distributions in a reaction system are often unavailable. Systems operating at a complex-balanced equilibrium are a notable exception in that they admit tractable product-form distributions [21][22][23][24]. Steady-state distributions have also been characterised in terms of generating functions in a growing collection of simple models that are not complex-balanced [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Section 3 contains the derivation of the LNA results and cross-validates them with large-scale kinetic Monte Carlo simulations. Section 4 focuses on a special case in which the model admits a product-form distribution predicted by the Chemical Reaction Network Theory [23,24]. Section 5 introduces a QSS approximation and shows that it can outperform the LNA in a specific parametric regime.…”
Section: Introductionmentioning
confidence: 99%